Technical-tactical actions of continuity in professional and amateur padel: a comparative analysis by sex and level - Ihsan, M.; Kwok, V.; Wong, H. Y.; Girard, O.; James, C. (International Journal of Sports Physiology and Performance, 2025)
Purpose: The relationship between shot type and court surface in technical-tactical continuity actions was analyzed, considering player sex and competition level in padel.